"Managing the Migration From Military to Civil Society": Motivation Model for Socioeconomic Needs in Resettlement of Veterans in India. (July 2016) - Maharajan, K.; Krishnaveni, R.
An estimated 70, 000 personnel are annually released at the prime of life from the Indian armed forces to maintain a youthful service profile. The migration of veterans in search of a second career to civil society involves managing crucial socioeconomic needs. This article examines the resettlement needs of veterans using survey research which measured resettlement needs of air force veterans in two distinct districts (regions) in India ( N = 400). The analysis reveals that the educational needs of dependent children are on top of the agenda followed by the need to find civilian employment. This study also develops a socioeconomic need continuum and a motivation model of resettlement.